2023
DOI: 10.1101/2023.01.07.523089
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The mechanosensitive ion channel Piezo1 contributes to ultrasound neuromodulation

Abstract: Transcranial low-intensity ultrasound is a promising neuromodulation modality, with the advantages of non-invasiveness, deep penetration, and high spatiotemporal accuracy. However, the underlying biological mechanism of ultrasonic neuromodulation remains unclear, hindering the development of efficacious treatments. Here, the well-known Piezo1, was studied through a conditional knockout mouse model as a major molecule for ultrasound neuromodulation ex vivo and in vivo. We showed that Piezo1 knockout in the righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 59 publications
(85 reference statements)
0
21
0
Order By: Relevance
“…Previous studies have concluded that regions exhibiting higher Piezo1 expression demonstrate an increased response to ultrasound. [35] We also observed the targeted effects of LFS on PKF. The LFS-induced inhibition of migration induced by LFS is more significant in PKF cells than in NIH 3T3 or HFF-1 cells.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies have concluded that regions exhibiting higher Piezo1 expression demonstrate an increased response to ultrasound. [35] We also observed the targeted effects of LFS on PKF. The LFS-induced inhibition of migration induced by LFS is more significant in PKF cells than in NIH 3T3 or HFF-1 cells.…”
Section: Discussionmentioning
confidence: 72%
“…[67] Recent investigation of the underlying biological mechanisms of ultrasonic neuromodulation's demonstrated the functional expression of Piezo1 channel in different regions of the brain, including both the right motor cortex and central amygdala with the latter exhibiting greater sensitivity to US. [68] In the same context of ultrasonic neuromodulation, Yoo et al investigated the biomolecular and cellular mechanisms by which FUS excites primary cortical neurons. Their results established that US excites neurons via direct mechanical force leading to extracellular calcium influx.…”
Section: Microbubble-free Ion Channel Stimulationmentioning
confidence: 99%
“…Though the exact physical interactions between US and cellular membranes remain unknown, mechanosensitive channels are generally thought to be critical in mediating cellular signaling changes during US neuromodulation [14][15][16][17][18][19] . Many mechanosensitive channels are widely expressed in the brain 20 , such as the two-pore potassium K2P family [20][21][22] , hyperosmolality-gated calcium-permeable TMEM63 family 20,23 , mechanosensitive cation channel Piezo family 20,24,25 , and the transient receptor potential TRP families 19,20,[26][27][28][29][30] . Among the large number of mechanosensitive channels, several members of the K2P, TRP and Piezo1 families have been implicated in ultrasound neuromodulation 19,[24][25][26]31,32 (Supplemental Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Many mechanosensitive channels are widely expressed in the brain 20 , such as the two-pore potassium K2P family [20][21][22] , hyperosmolality-gated calcium-permeable TMEM63 family 20,23 , mechanosensitive cation channel Piezo family 20,24,25 , and the transient receptor potential TRP families 19,20,[26][27][28][29][30] . Among the large number of mechanosensitive channels, several members of the K2P, TRP and Piezo1 families have been implicated in ultrasound neuromodulation 19,[24][25][26]31,32 (Supplemental Table 1). For example, genetic knockout of Piezo1 25 or knockdown of Trpm2 26 reduced US-mediated neural and behavioral responses in mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation